2021
DOI: 10.3389/fmolb.2021.680940
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Peptides Derived From Lycosa Erythrognatha Venom: Interaction With Phospholipid Membranes and Activity Against Resistant Bacteria

Abstract: Superbugs are a public health problem, increasing the need of new drugs and strategies to combat them. Our group has previously identified LyeTxI, an antimicrobial peptide isolated from Lycosa erythrognatha spider venom. From LyeTxI, we synthesized and characterized a derived peptide named LyeTxI-b, which has shown significant in vitro and in vivo activity. In this work, we elucidate the interaction of LyeTxI-b with artificial membranes as well as its effects on resistant strains of bacteria in planktonic cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Likewise, the same PEG-induced spatial impairment can be the cause of a smaller lytic activity for LyeTx I-bPEG, as evidenced by its smaller calcein release percentage. Nevertheless, the interaction mechanism of LyeTx I-b, mainly driven by electrostatic forces ( Reis et al, 2021 ), does not seem to be significantly altered after PEGylation, since a smaller calcein release was observed for both peptides in the presence of zwitterionic LUVs in comparison with anionic LUVs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the same PEG-induced spatial impairment can be the cause of a smaller lytic activity for LyeTx I-bPEG, as evidenced by its smaller calcein release percentage. Nevertheless, the interaction mechanism of LyeTx I-b, mainly driven by electrostatic forces ( Reis et al, 2021 ), does not seem to be significantly altered after PEGylation, since a smaller calcein release was observed for both peptides in the presence of zwitterionic LUVs in comparison with anionic LUVs.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the search for novel antimicrobial agents against superbugs is an urgent need, and antimicrobial peptides (AMPs) stand out from their conventional counterparts due to their bactericidal potential, anti-inflammatory activity, and modulation of the immune system ( Kang et al, 2012 ; Fosgerau and Hoffmann, 2015 ; Zhang and Gallo, 2018 ; Chen and Lu, 2020 ). Fungal and bacterial cell membrane phospholipids are known targets for these biopolymers, which act by increasing permeability, leading to leakage of intracellular material and subsequent death of the microorganism ( Brito et al, 2021 ; Reis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…LyeTx I-b is a synthetic peptide differing from LyeTx I by lacking a cysteine residue at position 16. LyeTx I-b was active against diverse bacteria in in vitro and in vivo assays [ 35 , 36 , 37 ] and presented a higher affinity in phospholipid membrane assays compared to LyeTx I [ 38 ]. Furthermore, a previous study conducted by our group showed that intraocular injection of LyeTx I-b suppressed neovascularization in ocular disease using a chorioallantoic membrane model [ 39 ].…”
Section: Introductionmentioning
confidence: 99%